A novel minimal motif for left-handed G-quadruplex formation - Das, Poulomi (2021)
A recent study on the left-handed G-quadruplex (LHG4) DNA revealed a 12-nt minimal motif GTGGTGGTGGTG with the ability to independently form an LHG4 and to drive an adjacent sequence to LHG4 formation. Here we have identified a second LHG4-forming motif, GGTGGTGGTGTG, and determined the X-ray crystal structure of an LHG4 involving this motif. Our structural analysis indicated the role of split guanines and single thymine loops in promoting LHG4 formation.